ASEAN's Fledgling Debt Securities Markets: More tasks Ahead - Mario B. Lamberte (Philippine Institute for Development Studies (PIDS), 2002)
ASEAN economies have long recognized the importance of developing a deep and broad domestic debt securities market to complement the banking system in efficiently mobilizing and allocating financial resources. However, it was only in the early 1990s that they started to make bold steps to build a vibrant domestic debt securities market. The East Asian financial crisis has further strengthened their resolve to accelerate the development of their domestic debt security markets and reduce reliance on bank lending. Still, the overall performance of the debt security markets in these economies leaves much to be desired. Among the five ASEAN member countries, Singapores debt market is moving ahead of the rest, while those of the Philippines and Indonesia lag far behind. The paper has identified some tasks that ASEAN economies must do to accelerate the development of their fledgling debt securities markets. While some of the ASEAN member countries have already done some of these tasks, the Philippines still needs to start doing practically all of them.
Keywords: 330; ASEAN; Fremdkapital; Wertpapierhandel; ASEAN-Staaten